2009 Sixth International Conference on Information Technology: New Generations 2009
DOI: 10.1109/itng.2009.302
|View full text |Cite
|
Sign up to set email alerts
|

A Proactive Approach to Preventing Phishing Attacks Using Pshark

Abstract: Phishing is an online scam used to dupe people out of their personal information for the purpose of defrauding them. This paper presents a conceptual design for removing phishing pages that have been uploaded on a website, potentially without knowledge of the website owner or host server. Initially the system is alerted to the presence of a phishing page upon receiving the Phisher's solicitation e-mail. Next the system retrieves the location, IP address and contact information of the host server using a tracki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Phishing is the process of enticing people into visiting fraudulent websites and persuading them to enter their personal information. Numbers of phishing email are spread with the aim of making web users believe that they are communicating with a trusted entity [2]. Phishing deployed by use advanced technical means.…”
Section: State-of-the-art Of E-mail Phishingmentioning
confidence: 99%
See 1 more Smart Citation
“…Phishing is the process of enticing people into visiting fraudulent websites and persuading them to enter their personal information. Numbers of phishing email are spread with the aim of making web users believe that they are communicating with a trusted entity [2]. Phishing deployed by use advanced technical means.…”
Section: State-of-the-art Of E-mail Phishingmentioning
confidence: 99%
“…A lot of antiphishing techniques are in vogue to draw a dividing line or identify between the fake and the authentic websites, however due to the vast amount and new harmful tactics of phisher, the challenges are yet being faced. [2] [3] For instance, a system can be technically safe and secure enough against password theft, however naive users may leak their sensitive information if an attacker lead them to update their sensitive information such as username, passwords via a given Hypertext Transfer Protocol (HTTP) link [4]. It could ultimately breach the security of the system, web vulnerabilities like obfuscated/phishing URLs can be used by phishers to craft far more influencing socially-engineered messages.…”
Section: Introductionmentioning
confidence: 99%
“…Pshark is an approach proposed by Shah et al [19] to detect and eliminate the identified phishing web page from host server. The WHOIS database is used to retrieve the information about the page.…”
Section: Related Workmentioning
confidence: 99%
“…If no anti-phishing tool is installed or the user has not updated the anti-phishing program, then there is no layer of protection. This is referred to as passive antiphishing [16]. It is because the approach only locally protects the user from a phishing attack but does not make any effort to stop or remove the Phisher at the source.…”
Section: Related Work and Literature Reviewmentioning
confidence: 99%